Pelatihan Pembuatan Puding Kreatif guna Meningkatkan Perekonomian Keluarga Jemaat GPIA Sidoasri Malang - Jeli Megawati; Maria Susanti (Institut Nalanda, 2026)
: This community service activity aimed to equip female members and youth women of GPIA Sidoasri congregation in Malang with practical skills in creative pudding production as a means to improve household income, grounded in the biblical mandate of Proverbs 10:4 which teaches that diligent hands lead to prosperity. Ten participants attended the two-day training held on January 21–22, 2026, covering material identification, raw ingredient costing, equipment use, and hands-on pudding-making practice. Participants learned to produce two products: fried-egg-style pudding and Regal biscuit pudding. Economic analysis showed that fried-egg pudding yields a 100% profit margin, while Regal pudding yields 40–50% profit margin. Post-training evaluation confirmed that participants successfully executed pre-order sales to congregation members and local residents in Sidoasri. This study employs a qualitative participatory approach with observation and structured interview as data collection instruments. The results demonstrate that skill-based community service, when rooted in theological principles and practical economic training, effectively empowers marginalized communities toward financial self-sufficiency.